2016
DOI: 10.1111/ene.13201
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality following poliomyelitis – a lifelong follow‐up

Abstract: Poliomyelitis has significant long-term consequences on morbidity and mortality of both paralytic and non-paralytic cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A study from Denmark showed that infectious diseases, mental disorders, diseases of the nervous system and diseases of the circulatory and respiratory systems were more common among polio survivors (25). Similarly, a study from Taiwan showed that polio patients have a higher risk of hypertension, ischaemic heart disease, stroke, rheumatoid arthritis and chronic pulmonary diseases (26).…”
Section: Discussionmentioning
confidence: 99%
“…A study from Denmark showed that infectious diseases, mental disorders, diseases of the nervous system and diseases of the circulatory and respiratory systems were more common among polio survivors (25). Similarly, a study from Taiwan showed that polio patients have a higher risk of hypertension, ischaemic heart disease, stroke, rheumatoid arthritis and chronic pulmonary diseases (26).…”
Section: Discussionmentioning
confidence: 99%
“…Neuromuscular disorders encompassing primary myopathies, neuropathies and diseases of the neuromuscular junction are together a group of diseases that are often challenging to disentangle diagnostically . Many of these have a genetic basis and novel causative mutations continue to be identified and the clinical phenotype of existing mutations more clearly defined .…”
mentioning
confidence: 99%